2018
DOI: 10.1159/000493096
|View full text |Cite
|
Sign up to set email alerts
|

High-Salt Diet Gets Involved in Gastrointestinal Diseases through the Reshaping of Gastroenterological Milieu

Abstract: Background: Gastrointestinal (GI) diseases are known to be largely influenced by one’s lifestyle and dietary uptake. A high-salt diet (HSD) is well recognized as a risk factor for cardiovascular complications, hypertension, and metabolic syndromes. However, the relationship between an HSD and the GI system, which is the compartment that comes in direct contact with exogenous stimulants, has not been fully explored. Aims: We seek to better understand the complexity of the pathogenic effects of an HSD in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 60 publications
1
24
0
1
Order By: Relevance
“…3,4 The pathways involved in the induction of T H 17 cells after high-salt intake are related to activation of the p38/mitogen-activated protein kinase, nuclear factor of activated T cells and serum glucocorticoid-regulated kinase pathways (Table 1). [3][4][5][6][7] Notably, recent investigations showed that high-salt intake is involved in the induction of inflammatory reactions through disturbance of the gut microbiota (see recent reviews 2,8 ). In this regard, Wilck et al found that a high-salt diet disturbs the murine gut microbiome and induces neuroinflammation through T H 17 expansion in the EAE-affected murine model.…”
Section: New Findings On the Role Of High-salt Intake In Induction Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The pathways involved in the induction of T H 17 cells after high-salt intake are related to activation of the p38/mitogen-activated protein kinase, nuclear factor of activated T cells and serum glucocorticoid-regulated kinase pathways (Table 1). [3][4][5][6][7] Notably, recent investigations showed that high-salt intake is involved in the induction of inflammatory reactions through disturbance of the gut microbiota (see recent reviews 2,8 ). In this regard, Wilck et al found that a high-salt diet disturbs the murine gut microbiome and induces neuroinflammation through T H 17 expansion in the EAE-affected murine model.…”
Section: New Findings On the Role Of High-salt Intake In Induction Ofmentioning
confidence: 99%
“…1 In animal models of MS (e.g. [3][4][5][6][7] Notably, recent investigations showed that high-salt intake is involved in the induction of inflammatory reactions through disturbance of the gut microbiota (see recent reviews 2,8 ). 1 In addition to these important findings, new investigations have shown the role of high-salt intake in the pathogenesis of MS through induction of severe neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium chloride from dietary salt supplies essential electrolytes to the human body, and it plays a vital role in maintaining the stability of the intracellular and extracellular environments (Li et al, 2018). Despite its essential involvement in many physiological activities, too much salt uptake has been identified as detrimental for many well-recognized and age-related diseases such as myocardial hypertrophy, hypertension and cancer (Maruyama et al, 2015;Xu et al, 2018a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exercise results in a number of physiological adaptations such as an increase angiogenesis and antioxidant ability that improves muscle performance and enhances the resistance of the muscle to fatigue (Ahmadiasl et al, 2012;Petersen and Greene, 2008). However, a HSD can impair skeletal muscle performance by inhibiting its angiogenesis and increasing oxidative stress (Bernardi et al, 2012;Lenda and Boegehold, 2002;Li et al, 2018;Petersen and Greene, 2008). Therefore, these studies suggest that in regards to health, exercise training and a HSD are in opposition to each other.…”
Section: Introductionmentioning
confidence: 99%
“…For a long period of time, dietary management and caloric restriction were generally focused on three major energy sources, carbohydrate, fat and protein, while the role of noncaloric nutrients, namely salt (sodium chloride), is less appreciated. Besides the well-recognized effect on the cardiovascular system, the HSD -SGK1 axis is also suggested to engage with gastroenterological disorders, obesity-related metabolic syndrome and autoimmune diseases (8,18,19). Therefore, investigations on the multifaceted effect of SGK1 not only help to enrich our understanding of nutritional regulation but provide valuable targets for clinical interventions as well.…”
Section: Introductionmentioning
confidence: 99%